Răspuns :
a) -3\2
d)3x=5
x=5\3
e)2x=0,2
x=0,2\2
x=0,1
f)2x+2-3=2
2x-1=2
2x=2+1
2x=3
x=3\2
g)-1\5
d)3x=5
x=5\3
e)2x=0,2
x=0,2\2
x=0,1
f)2x+2-3=2
2x-1=2
2x=2+1
2x=3
x=3\2
g)-1\5
a) -2x=3 <=> x=-3/2
b) 3(x+1) = -5*2 <=>3x+3=-10 <=> 3x=-13 <=> x= -13/3
c) 3x = 2(x+1) <=> 3x=2x+2 <=> x=2
d) 3x=5 <=> x=5/3
e) 2x=0,2 <=> x= 0,1
f) 2x+2-3=2 <=> 2x=3 <=> x=3/2
g) x-1 = 2x*3 <=> x-1 =6x <=> x=-1/5
b) 3(x+1) = -5*2 <=>3x+3=-10 <=> 3x=-13 <=> x= -13/3
c) 3x = 2(x+1) <=> 3x=2x+2 <=> x=2
d) 3x=5 <=> x=5/3
e) 2x=0,2 <=> x= 0,1
f) 2x+2-3=2 <=> 2x=3 <=> x=3/2
g) x-1 = 2x*3 <=> x-1 =6x <=> x=-1/5